Karakteristik Pasien Otitis Eksterna Dan Otitis Media Tahun 2018-2019 (Sebelum Pandemi Covid-19) Dan Tahun 2020-2021 (Selama Pandemi Covid-19) Di Rsud Sayang Rakyat Provinsi Sulawesi Selatan - fitrah putra irwan; Dahlia; Rismayanti; Ahmad Ardhani Pratama; Meriam Melinda (Universitas Muslim Indonesia, 2023)
There is no data that shows comparisons between patients before and during the covid-19 pandemic, especially in otitis externa and otitis media, so this study was made to obtain data that will be the latest guidelines, so researchers are interested in researching the incidence rate and factors that cause the quantity of patients from these hospitals in this study. To find out the Characteristics of Otitis Externa and Otitis Media Patients in 2018-2019 (Before the Covid-19 Pandemic) and in 2020-2021 (During the Covid-19 Pandemic) at the Rsud sayang Rakyat of South Sulawesi Province. This research is a descriptive study with a cross-sectional design conducted at the Sayang Rakyat Regional Hospital of South Sulawesi Province in November 2022. The population of this study is all patients otitis externa and otitis media of Hospital sayang Rakyat Province of South Sulawesi in 2018-2021. The results of the study obtained from collecting medical record data, it was found that dominant women 64 (7%) compared to men, the highest prevalence of otitis externa aged 11-20 years 79 (19%) cases in 2019, the lowest <11 years 11 (8%) cases in 2021, and the most otitis media aged <11 years 69 (26%) cases in 2019, the lowest <11 years 10 (10%) cases in 2021. Patient comparison data for 2018-2019 more 608 (52%) cases than in 2020-2021 otitis externa and otitis media patients in 2018-2019 (before the covid-19 pandemic) and 2020-2021 (during the covid-19 pandemic).